Inclusive Education Management through Community Service Programs: Efforts to Achieve Access and Educational Equity - Muh. Hanif; Syamsu Rijal (PT. LITERASI SAINS NUSANTARA, 2026)
This study aims to examine inclusive education management through community service programs as an effort to achieve access and educational equity. The approach used is qualitative with a literature review research design, specifically intended to enrich references related to community service within the context of inclusive education. Data were collected from various scientific sources through Google Scholar and other credible websites within the period 1964–2026. From 50 articles obtained in the initial stage, a rigorous selection process based on relevance, quality, and topic suitability resulted in 26 articles being analyzed. The analysis technique employed was descriptive qualitative by identifying patterns, themes, and relationships among concepts. The findings indicate that the success of inclusive education is strongly influenced by community involvement, social support, and collaboration among stakeholders. Community service programs play a strategic role as instruments that bridge the gap between theory and practice, while also enhancing inclusive literacy in society. However, challenges remain in integrating these programs into a comprehensive education management system. Therefore, strengthening management, improving human resource capacity, and developing sustainable community-based models are necessary to optimally support the implementation of inclusive education.